2011
DOI: 10.1111/j.1365-2141.2010.08549.x
|View full text |Cite
|
Sign up to set email alerts
|

The non‐relapse mortality rate for patients with diffuse large B‐cell lymphoma is greater than relapse mortality 8 years after autologous stem cell transplantation and is significantly higher than mortality rates of population controls

Abstract: SummaryHigh dose chemotherapy followed by autologous stem cell transplantation (ASCT) is the preferred treatment modality for patients with relapsed or refractory diffuse large B‐cell lymphoma (DLBCL). To assess long‐term outcomes of these patients, we retrospectively analysed data from 309 consecutive patients who underwent ASCT for DLBCL between 1994 and 2006. We found that non‐relapse mortality (NRM) became the major cause of death beginning approximately 8 years after ASCT. The most common causes of NRM du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
4
25
0
1
Order By: Relevance
“…15 In the current study, SMNs were the most common cause of non-relapse mortality among aHCT recipients, accounting for 9% of all deaths, and placing the cohort at a 3.9-fold increased risk of cancer-related death; these findings are similar to previous studies. 3, 1618 HL patients, were at a 14.8-fold increased risk of SMN-related death compared to the general population. Previous studies have demonstrated that the risk of developing therapy-related leukemia is significantly elevated among patients with HL and NHL treated with aHCT, and carries a dismal prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…15 In the current study, SMNs were the most common cause of non-relapse mortality among aHCT recipients, accounting for 9% of all deaths, and placing the cohort at a 3.9-fold increased risk of cancer-related death; these findings are similar to previous studies. 3, 1618 HL patients, were at a 14.8-fold increased risk of SMN-related death compared to the general population. Previous studies have demonstrated that the risk of developing therapy-related leukemia is significantly elevated among patients with HL and NHL treated with aHCT, and carries a dismal prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…With a median follow‐up of 7.6 years and with 68% having received total body irradiation (TBI)–based preparative regimens, the cohort had a 13‐fold increased risk of late death in comparison with the general population. Subsequent reports have confirmed an increased risk of late mortality . In addition, mostly single‐center studies have reported high rates of organ impairment, functional limitations, and subsequent malignant neoplasms (SMNs) in auto‐HCT survivors …”
Section: Introductionmentioning
confidence: 93%
“…Subsequent reports have confirmed an increased risk of late mortality. [10][11][12][13] In addition, mostly single-center studies have reported high rates of organ impairment, functional limitations, and subsequent malignant neoplasms (SMNs) in auto-HCT survivors. [13][14][15] To address the gaps in the literature, we selected a representative, multicenter cohort of 2-year disease-free survivors of auto-HCT for cHL or DLBCL who were reported to the Center for International Blood and Marrow Transplant Research (CIBMTR).…”
Section: Introductionmentioning
confidence: 99%
“…Although patients usually have immune reconstitution after this transplantation procedure, T and B cell function can be impaired for a prolonged period. Follow-up of these patients has shown them to be at increased risk for non-relapse mortality, with up to 13% dying due to an infectious disease during long-term follow-up [8]. …”
Section: Discussionmentioning
confidence: 99%
“…This immunodeficiency is due to BTK mutations that result in deficient BTK function. These children often suffer from opportunistic infections during early life [8]. …”
Section: Discussionmentioning
confidence: 99%